Barriers and mechanisms to the development of palliative care in Aceh, Indonesia. - Wilson, Fiona; Wardani, E.; Ryan, T.; Gardiner, C.; Talpur, A. (Progress in Palliative Care, 2024)
The aim of this study was to identify barriers and mechanisms in the development of palliative care in the province of Aceh, North West Indonesia. Several factors, including an ageing population, have increased palliative care needs in the region; however, as with many low to middle income countries (LMICs), palliative care is not well established or integrated into mainstream health care services. Consequently, many people may experience serious health-related suffering (SHRS) at the end-of-life. Qualitative semi-structured interviews and focus groups were conducted with key stakeholders in Aceh, Indonesia and a semi-structured interview guide prompted an exploration of palliative care provision, including barriers and enablers. Interviews were digitally recorded, transcribed, and analysed using the principles of thematic analysis. Eight interviews and two focus groups were conducted with medics (n = 6), nurses (n = 7), hospital management (n = 1) and religious/cultural leaders (n = 2). The findings indicate that all participants recognise a need to reduce SHRS and a growing impetus to embed a culturally salient and sustainable model of palliative care within the Aceh healthcare system. The following four themes indicate key areas for further focus: (1) Local vision and leadership, (2) Prioritisation of palliative care policy and funding, (3) Access to palliative care in community and public services, and (4) supporting palliative care in the cultural context of Sharia law, family, and faith. Future expansion requires the identification of a culturally and socioeconomically salient package of palliative care which operates across rural community and acute care settings and is informed by further evaluation and evidence.